2017
DOI: 10.1212/wnl.0000000000004299
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound examination of the pupil suggestive for carotid dissection

Abstract: A 51-year-old man presented to our emergency department with persistent right cervical pain. Neurologic examination was unremarkable, and no anisocoria was reported. Using a linear ultrasound probe, the pupillary diameters were measured at rest, under direct/consensual light stimulus, and after elicitation of the ipsilateral ciliospinal reflex (CR), evoked by applying a painful stimulation (pinching) at the base of the neck on the trapezius muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Also, the new method proposed here may be a useful and practical tool to reveal subclinical changes in pupillary function. For example, in patients with mild clinical symptoms, with clinically suspected carotid dissection or brainstem injury, pupillary ultrasound assessment may help select patients suitable for emergency neuroimaging examination 22 . This technique may have potential applications in the study of pupillary function in neurodegenerative and neuroin ammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the new method proposed here may be a useful and practical tool to reveal subclinical changes in pupillary function. For example, in patients with mild clinical symptoms, with clinically suspected carotid dissection or brainstem injury, pupillary ultrasound assessment may help select patients suitable for emergency neuroimaging examination 22 . This technique may have potential applications in the study of pupillary function in neurodegenerative and neuroin ammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…To test the CR, a painful stimulation (pinching) should be applied at the base of the neck on the trapezius muscle ipsilaterally to the tested eye. The stimulus should be vigorous in order to achieve a reliable CR [30] (Fig. 25.3).…”
Section: Pupil: Ultrasound Examinationmentioning
confidence: 99%
“…In 2009, Sargsyan et al showed in a traumatized patient with eyelid swelling that ultrasound examination of the eye could provide clear and precise visualization of spatial and temporal parameters of the pupils [10]. More recently, we pointed out the utility of ultrasound pupillometry (UP) in a patient with spontaneous dissection of the distal internal carotid artery segment [11]. In light of these findings, we aimed to establish the feasibility and reproducibility of UP in comparison with IVP and obtain values for PLR and CR in neuro-ophthalmologically healthy subjects.…”
Section: Introductionmentioning
confidence: 96%